Changes in heart rate variability in patients with hypertension under outpatient stage treatment - V. I. Koshlia; Mouna Ben-Abid (Zaporožskij Medicinskij Žurnal)
Actuality of the heart rate variability study in patients with hypertension is underlined with high risk of hypertension complications development and the influence of the autonomic nervous system that changes the tone, affects not only the course of the disease but also increases the risk of death.